2008
DOI: 10.1088/0741-3335/50/12/124010
|View full text |Cite
|
Sign up to set email alerts
|

MHD instabilities in magneto-plasma-dynamic thrusters

Abstract: Magneto-plasma-dynamic thrusters (MPDTs) act as electromagnetic plasma accelerators and represent a high power, electric propulsion option for primary space missions. One of the major problems facing MPDT operation is the onset of a critical regime, which is found when the power is increased beyond a threshold value, depending mainly on the thruster geometry, the type and mass flow rate of the propellant and the intensity of the magnetic field applied. In this regime, large fluctuations in the electrode voltag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Furthermore, some of these thrusters are operated in a pulsed regime, leading to a pulsed behavior of the plasma plume, making the investigation of its influence on the radio communication complex. Even for the thrusters operated in a stationary regime, they have been shown to exhibit instabilities and intrinsic plasma oscillations, leading to a temporal modulation of the plasma density, such as for example the instabilities of Hall thruster 34 , the electron instabilities in Magnetoplasmadynamic thruster 35 and the "onset phenomena" 36 , or the poorly understood instabilities in microwave discharge ion thrusters 37 . In order to investigate the effect of the plasma plume on the communication link in simulation, a spatio-temporal description of the plasma plume would be required.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, some of these thrusters are operated in a pulsed regime, leading to a pulsed behavior of the plasma plume, making the investigation of its influence on the radio communication complex. Even for the thrusters operated in a stationary regime, they have been shown to exhibit instabilities and intrinsic plasma oscillations, leading to a temporal modulation of the plasma density, such as for example the instabilities of Hall thruster 34 , the electron instabilities in Magnetoplasmadynamic thruster 35 and the "onset phenomena" 36 , or the poorly understood instabilities in microwave discharge ion thrusters 37 . In order to investigate the effect of the plasma plume on the communication link in simulation, a spatio-temporal description of the plasma plume would be required.…”
Section: Methodsmentioning
confidence: 99%
“…Coaxial gun plasma sources have been extensively studied over the recent decades for a variety of applications. These include plasma refueling for fusion machines [1][2][3][4], as thrusters for space propulsion [5,6], simulations of astrophysical phenomena [7][8][9][10], acceleration of dust particles [11,12], type I edge localized mode (ELMs-I) simulation for ITER [13][14][15][16][17] and studies of magnetic field reconnection and instabilities in plasmas [18][19][20]. Based on this wide applicability, there is great interest in understanding the discharge characteristics of coaxial plasma guns and measuring the physical properties (density, ejection velocity, temperature, etc) of plasma.…”
Section: Introductionmentioning
confidence: 99%
“…As MPDTs are typically coaxial-type devices, achieving line-of-sight within the thruster requires unusual thruster geometries and/or cutouts in the sides of the thruster. [12][13][14] While modifications to the physical geometry of the MPDT are not ideal and can introduce additional variations in an already complicated device, Kinefuchi et al 12 reasoned and demonstrated that a 2-dimensional geometry would not introduce anomalous behavior from that of the typical coaxial accelerator.…”
Section: Introductionmentioning
confidence: 99%